2021
DOI: 10.1111/jzs.12529
|View full text |Cite
|
Sign up to set email alerts
|

Integrative systematics of Neotropical porcupines ofCoendou prehensiliscomplex (Rodentia: Erethizontidae)

Abstract: Coendou comprises the most speciose genus in Erethizontidae, with 15 currently recognized species. Although several taxonomic studies in the last two decades have unveiled part of its diversity, the most widespread Neotropical taxon Coendou prehensilis has received limited attention. Here, we combined morphological and molecular datasets to infer the phylogenetic relationships of the species in the genus and revise the taxonomy of the C. prehensilis complex. We found four morphotypes and three well-supported m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 76 publications
2
17
0
4
Order By: Relevance
“…Erethizontids are characterized mainly by having their fur modified into quills, and some species have a bulbous snout and a long dorsally prehensile tail, which is an exclusive trait among prehensile-tailed mammals ( Emmons 1997 ; Voss 2015 ). Currently the 18 species of erethizontids are classified in three genera, with the genus Coendou comprising 16 species ( Menezes et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erethizontids are characterized mainly by having their fur modified into quills, and some species have a bulbous snout and a long dorsally prehensile tail, which is an exclusive trait among prehensile-tailed mammals ( Emmons 1997 ; Voss 2015 ). Currently the 18 species of erethizontids are classified in three genera, with the genus Coendou comprising 16 species ( Menezes et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the early 1990s, studies have clarified the taxonomic status and phylogenetic relationships among species of Coendou ( Handley and Pine 1992 ; Voss and Angermann 1997 ; Voss and da Silva 2001 ; Voss 2011 ; Feijó and Langguth 2013 ; Mendes Pontes et al 2013 ; Voss et al 2013 ), as well as its subgeneric classification (e.g., Menezes et al 2021 ). Additionally, knowledge of the distribution and natural history of Coendou species has advanced (e.g., Freitas et al 2013 ; Gregory et al 2015 ; Menezes et al 2020 ; Ramírez-Chaves et al 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…The Amazonian long-tailed porcupine Coendou (Coendou) longicaudatus Daudin, 1802 is a large arboreal Neotropical rodent that is widely distributed in the Amazon, east of the Andes, although its range is currently limited to the left bank of the Xingu River, being the only species of the genus occurring in the study area (Menezes et al 2021). From the dorsal view, it is characterized by a dark brown coloration, streaked with short white dashes (Menezes et al 2021).…”
mentioning
confidence: 99%
“…The Amazonian long-tailed porcupine Coendou (Coendou) longicaudatus Daudin, 1802 is a large arboreal Neotropical rodent that is widely distributed in the Amazon, east of the Andes, although its range is currently limited to the left bank of the Xingu River, being the only species of the genus occurring in the study area (Menezes et al 2021). From the dorsal view, it is characterized by a dark brown coloration, streaked with short white dashes (Menezes et al 2021). With respect to predation, there are occasional records of this porcupine being preyed upon by the ocelot Leopardus pardalis (Arias-Alzate et al 2017;Griffiths et al 2020) The individual in question was observed in the vicinity of the Samuel Hydroelectric Plant lake, near to the Samuel Ecological Station (latitude 9.060749; longitude 63.290839) at around 09:35 on July 9, 2021 (Figs.…”
mentioning
confidence: 99%
See 1 more Smart Citation